Handbook of Local and Regional Development. - Pike, Andy (Taylor & Francis, 2010)
The Handbook of Local and Regional Development provides a comprehensive statement and reference point for local and regional development. The scope of this handbook's coverage and contributions engages with and reflects upon the politics and policy of how we think about and practice local and regional development, encouraging dialogue across the disciplinary barriers between notions of 'local and regional development' in the Global North and 'development studies' in the Global South. With over 40 contributions from leading international scholars in the field, this handbook provides critical re.